2011
DOI: 10.1007/s10461-011-9919-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Gay Men’s Participation in Gay Community Life: Implications for HIV Surveillance and Research

Abstract: Successful antiretroviral treatments, achievements in gay acceptance and human rights, and internet use have prompted changes in gay socialising which create potential challenges for engaging with gay men for HIV surveillance and research. We used data from the Australian behavioural surveillance and explored (i) the relationship between community engagement and HIV related practices, and (ii) time trends in gay men's engagement with the gay community. Analyses were conducted using log-binomial regression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 22 publications
6
83
0
Order By: Relevance
“…As has been found in other samples of GBM (Roxburgh et al, 2015;Zablotska et al, 2012), men in this study reported rates of substance use that were substantially higher than in the adult male population as a whole. Whereas general population studies have found that about one in six (17.3%) adult men report recently using any illicit drug use, with 2.5% using recently using crystal methamphetamine (Roxburgh et al, 2015), half (50.5%) of men in the Flux study were found to recently use illicit drugs with 12.0% recently using crystal methamphetamine.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…As has been found in other samples of GBM (Roxburgh et al, 2015;Zablotska et al, 2012), men in this study reported rates of substance use that were substantially higher than in the adult male population as a whole. Whereas general population studies have found that about one in six (17.3%) adult men report recently using any illicit drug use, with 2.5% using recently using crystal methamphetamine (Roxburgh et al, 2015), half (50.5%) of men in the Flux study were found to recently use illicit drugs with 12.0% recently using crystal methamphetamine.…”
Section: Discussionsupporting
confidence: 80%
“…The characteristics of both the enrolled and the anonymous paricipants in the Flux sample, while somewhat younger, are otherwise comparable to those of other samples of Australian GBM (Lea et al, 2013b;Prestage et al, 2009a;Zablotska, Holt, & Prestage, 2012). We have demonstrated the ability to collect sensitive information while protecting participants' confidentiality and that participants will provide valid personal contact details to enable successful follow-up.…”
Section: Discussionmentioning
confidence: 67%
“…A measure of social engagement with gay men was included, it consisted of two items: time spent with gay friends with responses on a four-point scale ranging from 'none' to 'a lot'; and the proportion of friends who are gay, with responses on a five-point scale ranging from 'none' to 'all' (20). The items were added together to obtain a total score.…”
Section: Questionnairementioning
confidence: 99%
“…There is also a demonstrated significant protective outcome associated with social engagement among gay men with respect to lower risk for dementia, depression, and psychosocial risks (Glass et al, 2006). Conversely, social engagement has also been associated with HIV-positive serostatus, unprotected anal intercourse with regular partners, and drug use (Zablotska, Holt, & Prestage, 2012).…”
Section: Social Engagementmentioning
confidence: 99%